Optical interferometry for piezoelectric translation measurements - Reyna Ocas, Albert (2011)
In this work we used a simple Michelson interferometer to characterize the deformation of a piezoelectric material in function of voltage and frequency. We obtained the piezoelectric quality factors parameters, such as, the resonance frequency, the damping constant and the quality factor by simulating its behaviour like a driven oscillator.